Evaluation of Biosecurity Measures on a Commercial Swine Operation Using Glo Germ Powder as a Visible Learning Aid - Olivia L. Harrison; Payton L. Dahmer; Jordan T. Gebhardt; Chad B. Paulk; Jason C. Woodworth; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2021)
Glo germ, a fluorescent powder, was used to determine the efficacy of common biosecurity practices to prevent the powder from spreading to other areas within a commercial swine farm. The areas tested included an entry bench, the shower where all incoming personnel are required to shower upon farm entry and exit, the clean area following the shower, and inside the barn, which acted as the control with no biosecurity procedures in place given it is fully contained within the broader biosecurity measures of the facility. Pictures, from a standard iPhone, were taken before and after student and personnel movement to observe any differences in Glo Germ coverage. The percentage of Glo Germ coverage in the before and after pictures was evaluated once by 47 untrained panelists and averaged for each location and time point. The control area with no biosecurity measures in the barn had significantly more Glo Germ coverage than the other three locations (P<0.0001). There was no evidence of a difference in Glo Germ coverage between the entry bench, shower floor, or clean side of shower (P>0.05). In conclusion, the use of Glo Germ was successfully able to emulate disease entry into the farm and can be used as a learning aid to demonstrate the efficacy of entry benches, clean/dirty lines, and showers.
Keywords: swine; biosecurity; teaching aid